Pharmacokinetic and Safety Profiles of Repeated-dose Prophylactic Micafungin in Children and Adolescents Undergoing Hematopoietic Stem Cell Transplantation. Issue 1 (January 2015) - Albano, Edythe; Azie, Nkechi; Roy, Mike; Townsend, Robert; Arrieta, Antonio
<x xml:space="preserve">Abstract</x> Micafungin is a potent echinocandin antifungal that can be used for both prophylaxis and treatment of Candida infections. This open-label study assessed the pharmacokinetics and safety profile of prophylactic micafungin in children and adolescents (aged 4 mo to 16 y) undergoing hematopoietic stem cell transplantation. Patients received once-daily doses of either 1 or 1.5 mg/kg micafungin, based on their body weight, for 10 to 14 days. In total, 40 patients received micafungin. Area under the plasma micafungin concentration–time curve was highest in patients aged 6 to 11 years in the 1.5 mg/kg treatment group. Peak plasma micafungin concentration displayed no age-related differences, but was higher in the 1.5 mg/kg versus the 1 mg/kg group. Clearance at steady state by weight and volume of distribution by weight were considerably higher in patients aged 4 months to 5 years. Results from this study show that age and body weight affect micafungin pharmacokinetics in pediatric patients undergoing hematopoietic stem cell transplantation.